[tex]y - 4x - 3 = 0 \\ 2x + y + 2 = 0[/tex]
[tex] - 4x + y = 3 \\ 2x + y = - 2[/tex]
[tex] - 4x + y = 3 \\ 4x + 2y = - 4[/tex]
------------------------------------- +
[tex]y + 2y = 3 - 4[/tex]
[tex]3y = - 1[/tex]
[tex]y = - \: \frac{1}{3} [/tex]
[tex]2x + y + 2 = 0 \\ 2x + ( - \frac{1}{3} ) = - 2 \\ 2x = - 2 + \frac{1}{3} \\ 2x = - 2 \frac{1}{3} \\ x = - 2 \frac{1}{3} \div 2 \\ x = - \frac{7}{3} \div \frac{2}{1} \\ x = - \frac{7}{3} \times \frac{1}{2} \\ x = - \frac{7}{6 } \\ x = - 1 \frac{1}{6} [/tex]
Y=- 1/3
X= - 1 1/6
Pozdrowionka! ~Wika